السلطـــات الاستثنائيــة لرئيس الجمهورية - دراســـة تأصيليـــة مقارنــة - فاكية صلعي (My University, 2022)
Summary: Algeria's constitutional founder has endeavoured to give the President of the Republic very broad powers. s institutions, independence and sovereignty in the event of an actual aggression against the country ", such as his French counterpart, to confront abrupt and unusual circumstances by resorting to exceptional situations such as the power to determine a state of emergency or embargo if urgently necessary. Or about to happen, as a more dangerous situation than before. State of war ", following which the President declares a state of war and enables him to take all necessary action to confront it. However, these exceptional powers conferred upon the President of the Republic relating to internal security can be taken or declared only under constitutional restrictions, including: Substantive as well as formal requirements (through consultation of constitutional institutions) However, the theory of exceptional circumstances extended the powers of the President, which in turn resulted in the restriction of the constitutionally guaranteed rights and freedoms of individuals. Consequently, the President of the Republic has a constitutional status that has enabled him to deprive legislative and judicial powers of their original competence. ........................... ملخص : لقد حرص المؤسس الدستوري الجزائري على منح رئيس الجمهورية سلطات واسعة جدا ، مثل نظيره الفرنسي، لمواجهة ظروف مفاجئة وغير مألوفة من خلال اللجوء إلى الحالات الاستثنائية كسلطة تقرير حالة الطوارئ أو الحصار إذا دعت الضرورة الملحة إلى ذلك وكذلك الحالة الاستثنائية إذا كان هناك خطر يوشك أن يصيب مؤسسات الجمهورية واستقلالها وسيادة ترابها في حال وقوع عدوان فعلي على البلاد ، أو على وشك الحدوث ، كوضع أكثر خطورة من السابق ، يعلن الرئيس على إثرها حالة الحرب وتمكّنه من اتخاذ جميع الإجراءات اللازمة لمواجهتها. على أن هذه السلطات الاستثنائية الموكلة إلى رئيس الجمهورية والمتعلقة بالأمن الداخلي لا يمكن اتخاذها أو الإعلان عنها إلا في ظل قيود دستورية ، بما في ذلك: الشروط الموضوعية وكذلك الشروط الشكلية (عن طريق استشارة المؤسسات الدستورية ) ، إضافة لذلك تم تخويله أيضا سلطة التشريع بأوامر في حالات استثنائية كسلطة ذات صلة بالمجال التشريعي، وكذا سلطة اتخاذ تدابير ذات طابع قضائي وإنشاء محاكم خاصة، إلا أن نظرية الظروف الاستثنائية وسعت من سلطات الرئيس والتي بدورها والتي نتج عنها بالمقابل تضييق من حقوق وحريات الأفراد المكفولة دستوريًا. وبالتالي فرئيس الجمهورية يتمتع بمكانة دستورية مكنته من سلب السلطات التشريعية والقضائية من اختصاصها الأصلي. .................................. Résumé : Le fondateur de la Constitution algérienne s’est efforcé de donner au président de la République des pouvoirs très étendus. Institutions, indépendance et souveraineté en cas d’agression réelle contre le pays ", comme son homologue français, pour faire face à des circonstances abruptes et inhabituelles en recourant à des situations exceptionnelles telles que le pouvoir de déterminer l’état d’urgence ou d’embargo si nécessaire de toute urgence. Ou sur le point de se produire, comme une situation plus dangereuse qu’avant. État de guerre ", après quoi le Président déclare un état de guerre et lui permet de prendre toutes les mesures nécessaires pour y faire face. Toutefois, ces pouvoirs exceptionnels conférés au Président de la République en matière de sécurité intérieure ne peuvent être exercés ou déclarés que dans le cadre de restrictions constitutionnelles, y compris : Exigences de fond et de forme (par la consultation des institutions constitutionnelles) Toutefois, la théorie des circonstances exceptionnelles a élargi les pouvoirs du président, ce qui a entraîné la restriction des droits et libertés garantis par la Constitution des individus. Par conséquent, le Président de la République a un statut constitutionnel qui lui a permis de priver les pouvoirs législatif et judiciaire de leur compétence initiale.